The use of biochar and fertilizer to maximize the growth and yield of ginger on degraded alluvial soil - Masulili, Agusalim; Suryani, Rini; Kurniadi, Edi (Brawijaya University, 2025)
Degraded alluvial soil that is commonly used for growing ginger (Zingiber officinale) has many issues, such as deficiency in nutrients. To increase the yield of ginger, proper fertilizers along with soil improvement techniques must be employed. In this case, the study analyzed the combined effects of rice husk biochar and Mahkota NPK fertilizer on the yield and growth of ginger in alluvial soil. The study was performed using a completely randomized design arranged with two treatment factors. The first factor was the application of rice husk biochar consisting of three different levels: s1 (5 t/ha), s2 (10 t/ha), and s3 (15 t/ha). The second factor was the application of Mahkota NPK fertilizer consisting of three levels: m1 (50 kg/ha), m2 (150 kg/ha), and m3 (250 kg/ha). The results of this study showed that the treatment combination of rice husk biochar and Mahkota NPK fertilizer was highly significant in improving bulk density, total porosity, pH, organic C, total nitrogen, available phosphorus, and potassium of the Alluvial soil. The interaction also greatly affected plant growth in terms of height, tiller formation, and weight of fresh rhizomes. However, the number of leaves remained uninfluenced. The highest yield was obtained with s2m3 treatment (10 t/ha rice husk biochar and 250 kg/ha NPK fertilizer). From this result, it can be suggested that the application of rice husk biochar in combination with Mahkota NPK fertilizer has the potential to remedy degraded alluvial soils and improve the growth and yield of ginger in the soils.